Absolute volume of the rectum and AUC from rectal DVH between 25Gy and 50Gy predict acute gastrointestinal toxicity with IG-IMRT in prostate cancer. Issue 1 (December 2016) - Mirjolet, Céline; Walker, Paul; Gauthier, Mélanie; Dalban, Cécile; Naudy, Suzanne; Mazoyer, Frédéric; Martin, Etienne; Maingon, Philippe; Créhange, Gilles
Abstract Background To determine whether dose/volume specific endpoints (DVSE) or Area under the rectal DVH curve (rAUC) better predict acute gastrointestinal (GI) toxicity in prostate cancer patients treated with IMRT in the era of daily image guidance (IG-IMRT). Methods A set of DVSE was recorded from V25 to V75 (increments of 5Gy) (both in % and in cc) for 180 men. The rAUC was calculated for doses ranging between 25Gy and 50Gy (rAUC25–50 ). Univariate and multivariate logistic regressions were performed to determine the relationship between DVSE or rAUC25–50 and the appearance of any acute GI toxicity. Results The rates of acute grade 1 (G1), G2 and G3 GI toxicities were 53.3 %, 10.6 % and 1.1 %, respectively. No G4+ toxicity was observed. Rectal V25 to V75 expressed in % were not predictive of G ≥ 1 GI toxicity (p ≥ 0.12) whereas rectal V25 to V50 expressed in cc did correlate with GI toxicity G ≥ 1 (p ≤ 0.04). rAUC25–50 expressed in cc. Gy correlated significantly with the occurrence of any acute GI toxicity G ≥ 1 (p = 0.027). Conclusions The absolute volume of the rectum between 25Gy and 50Gy and rAUC25–50 could significantly predict any acute rectal toxicity in prostate cancer patients treated with daily IG-IMRT.